2009
DOI: 10.1080/00207140903310824
|View full text |Cite
|
Sign up to set email alerts
|

Hypnosis Treatment for Chronic Low Back Pain

Abstract: Chronic low back pain (CLBP) is a significant healthcare problem, and many individuals with CLBP remain unresponsive to available interventions. Previous research suggests that hypnosis is effective for many chronic pain conditions; however, data to support its efficacy for CLBP are outdated and have been limited primarily to case studies. This pilot study indicated that a brief, 4-session standardized self-hypnosis protocol, combined with psycho-education, significantly and substantially reduced pain intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
15
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 37 publications
4
15
0
Order By: Relevance
“…Hypnosis helped this patient to manage her symptoms of loin pain hematuria and improve her quality of life. These findings are consistent with treatment outcomes of other pain conditions using hypnosis (Mackey, 2010; Tan, et al 2010; Dufresne, et al, 2010; Patterson, et al, 2010; Eitner, et al, 2010; Kohen, 2010; Nash & Tasso, 2010). …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Hypnosis helped this patient to manage her symptoms of loin pain hematuria and improve her quality of life. These findings are consistent with treatment outcomes of other pain conditions using hypnosis (Mackey, 2010; Tan, et al 2010; Dufresne, et al, 2010; Patterson, et al, 2010; Eitner, et al, 2010; Kohen, 2010; Nash & Tasso, 2010). …”
Section: Discussionsupporting
confidence: 83%
“…Previous studies have found hypnotherapy to be effective for pain (Dufresne et al, 2010; Eitner, Bittner, Wichmann, Nickenig, & Sokol 2010; Elkins, Jensen, & Patterson, 2007; Mackey, 2010; Kohen, 2010; Nash & Tasso, 2010; Patterson & Jensen 2003; Patterson, Jensen, Wiechman, & Sharar, 2010; Tan, Fukui, Jensen, Thornby, & Waldman, 2010) as well as for symptoms of anxiety and depression associated with medical conditions (Barabasz & Watkins, 2005; Elkins et al, 2008). Hypnotherapy may be beneficial for the treatment of the physical and psychological symptoms associated with loin pain hematuria, however to our knowledge there have not been any previous reports.…”
mentioning
confidence: 99%
“…Hypnotherapy ( HYP ) , one of the first psychological therapies to be implemented in medical populations, has been linked to positive outcomes in a number of chronic diseases such as cancer, rheumatoid arthritis, HIV, fibromyalgia and chronic pain . Mechanistic studies suggest that HYP can have positive effects on immune parameters, with data supporting the effects of HYP on T‐cell expression of interferon‐gamma and interleukin‐2, increases in secretory immunoglobulin‐A and neutrophil adherence, and reductions in inflammatory markers such as erythrocyte sedimentation rate, C‐reactive protein and leucocyte activity .…”
Section: Introductionmentioning
confidence: 99%
“…Hypnoanalgesia has proved to be very effective in the treatment of pain, which includes chronic oncological pain (Cassileth and Keefe, 2010; Sohl et al, 2010), HIV neuropathic pain (Dorfman et al, 2013), pain during extraction of molars (Abdeshahi et al, 2013), pain associated to physical trauma (Patterson et al, 2010), pain in surgical procedures (Facco et al, 2013), pain associated to temporomandibular joint disorder (Abrahamsen et al, 2010), phantom limb (Mack et al, 2013), fibromyalgia (Derbyshire et al, 2009), pain in amyotrophic lateral sclerosis (Palmieri et al, 2012), acute pain in children (Yaster, 2010), lumbago (Tan et al, 2010, 2014), and pain in childbirth (Oster, 1994; VandeVusse et al, 2007; Abbasi et al, 2009), amongst others. This fact fits what Cajal suggested more than a century ago.…”
Section: Discussionmentioning
confidence: 99%